Safety and efficacy of aspirin after combined cerebral revascularization for ischemic moyamoya disease: A prospective study - Xue, Bingqian; Zhang, Shao; Guo, Gaochao; Wu, Ruiyu; Gu, Kaiwen; Zhao, Liming; Li, Chaoyue (Frontiers in Surgery, 2023)
ABSTRACT Objective: To analyze the safety and efficacy of regular aspirin use after combined cerebral revascularization in patients with ischemic moyamoya disease. Methods: From December 2020 to October 2021, a total of 326 patients diagnosed with ischemic moyamoya disease by global cerebral angiography and undergoing first-time combined cerebral revascularization at the Moyamoya Disease Diagnosis and Treatment Research Center of our hospital were selected. Combined cerebral revascularization: superficial temporal artery-middle cerebral artery (STA-MCA) +encephalo-duro-myo-synangiosis (EDMS).Patients were screened by 2 senior physicians according to established inclusion/exclusion criteria. Patients were divided into aspirin and non-aspirin groups based on whether they received regular oral aspirin after surgery. A total of 133 patients were enrolled in the aspirin group. A total of 71 patients (204 cases) were enrolled in the non-aspirin group. Related data were collected before and 1 year after surgery and statistically analyzed to assess the prognosis of both groups. Results: In the two groups, the mRS Score was significantly different after one year (P=0.023). TIA occurred in 26 patients (19.5%) in the aspirin group and 27 patients (38.0%) in the non-aspirin group within one year after surgery, and the difference between the two groups was statistically significant (P= 0.004). There was no significant difference in cerebral perfusion stage, the improvement rate of cerebral perfusion, Matsushima grading, bypass patency, and other complications within one year after the operation (P > 0.05). Conclusions: In patients with ischemic moyamoya disease who underwent combined cerebral revascularization, postoperative administration of aspirin can reduce the incidence of TIA without increasing the risk of bleeding, but it can not significantly improve the cerebral perfusion of the operation side, Matsushima grading, and bypass patency.